2021
DOI: 10.3390/ma14206136
|View full text |Cite
|
Sign up to set email alerts
|

Surface Structure Analysis of Initial High-Temperature Oxidation of SS441 Stainless Steel

Abstract: Chromia-forming ferritic stainless steel (FSS) is a highly promising interconnect material for application in solid oxide fuel cells. In this study, initial oxidation of chromium oxides was performed at 500–800 °C to understand the evolution of materials at an early stage. The structural variations in oxide scales were analyzed through scanning electron microscopy, energy dispersive spectroscopy (EDS), transmission electron microscopy (TEM), X-ray diffractometry (XRD), laser confocal microscopy (LSCM), X-ray p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…[7][8][9] Other than that, AISI 441. is a solid-solution strengthened steel with some alloying additions of Ti and Nb for stabilization and improved high-temperature strength. [8,9] Previous work has shown that AM of AISI 441 by laser-powder bed fusion (L-PBF) lead to excellent mechanical properties compared to the conventional material produced by casting and hot rolling, attributed to the finer structure with small grain size in the printed material. [12] Conventionally manufactured AISI 441 is usually used in the hot or cold rolled and heat-treated state.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Other than that, AISI 441. is a solid-solution strengthened steel with some alloying additions of Ti and Nb for stabilization and improved high-temperature strength. [8,9] Previous work has shown that AM of AISI 441 by laser-powder bed fusion (L-PBF) lead to excellent mechanical properties compared to the conventional material produced by casting and hot rolling, attributed to the finer structure with small grain size in the printed material. [12] Conventionally manufactured AISI 441 is usually used in the hot or cold rolled and heat-treated state.…”
Section: Introductionmentioning
confidence: 99%